Comparative efficacy of Telakucha (Coccinia indica) leaves and Amaryl(R) Tablet (Glimepiride) in induced diabetes mellitus in rat - Amanullah, A; Mostofa, M; Ahmed, BS; Das, AR (Journal of the Bangladesh Agricultural University, 2010)
Thirty healthy rats of both sexes weighing between 150 to 200 gm were selected from among the offspring and randomly divided into six equal groups and rats of Group A and Group B were kept as non hypoglycemic control and hypoglycemic control, respectively. After acclimatization hyperglycemia was induced in five groups of rats (B,C,D,E and F) by administering streptozotocin (STZ) intraperitoneally at a dose of 55 mg/kg body weight. After fifteen days of STZ injection, four groups of rats (C,D,E and F) were administered with Telakucha (Coccinia indica) and Amaryl(R) (Glimepiride) as per schedule dose and all the control and treated rats were closely observed during 14 days of treatment.The oral administration over 14 days of Telakucha (Coccinia indica) leaves extract significantly lowered blood glucose level but was not so potent as patent drug Amaryl(R) (Glimepiride). The herbal preparation also increased body weight but not to the extent caused by the patent drug Amaryl(R) . The Telakucha leaves at 750mg/kg body weight significantly reduced (30.73%) the blood glucose level from 31.24±0.36 mmol/L to 21.64±0.17 mmol/L and significantly increased (5.45%) the body weight from 181.96±21.10g to 191.87±12.42 g. Keywords: Glimepiride; streptozotocin; Telakucha; Diabetes DOI: 10.3329/jbau.v6i2.4831 J. Bangladesh Agril. Univ. 6(2): 335-339, 2008